Adaptation to the European Higher Education Area, after 13 years: the destruction of knowledge at Spanish universities - Pomares Cintas, Esther; Álvarez García, Francisco Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The authors present the evolution of the Spanish Public University over the last thirty years, underlining how the interest in making higher education an object of further profit-making led international investment groups in Europe to a transformation of the University that was embodied in the «Bologna Plan». This model fits into the objective of the European «common market», or what is the same, conceives the university as just another commodity. In this sense, the «Bologna system» has served as an ideal platform for channelling investments capable of generating early returns and recoveries from investment: it reduces the duration of studies and their depth, building the plans on the basis of generic knowledge and «very practical», with the ability to «exchange in the market». It embodies a paradigm shift of business profile in two directions: the student as client and the bureaucratized figure of the teacher-giver of classes. The idea of a university understood as a mere «vocational training» deprived of any transformative initiative of the world has developed in Spain under the rise of private universities, driven since the mid-1990s, which has contributed to a serious deterioration in the quality of teaching and has also perverted the system of recruiting teaching staff to the point of making it functional: a radically bureaucratic procedure, in which the teacher’s profile in tasks very different from teaching and research has a specific weight, whose production is subject to pre-eminently formal valuations based on editorial decisions.This has led to a multiplication of publications under the logic of «uniformity» and, above all, market «functionality». At the same time, with the clearly intended of boosting private institutions, the budget of public universities, and the research in public institutions, has been cut, and university teaching staff has been made precarious to unacceptable limits. The public university, ostracized.The authors emphasize the need to carry out, with public funds, an urgent rescue of the public Spanish University, in order to restore it from its foundations and thus contribute to a change in the economic development model that Spain needs, which will even allow to survive future pandemics with greater solvency.
Keywords: rescue of public university; European Common Market»; Bologna Plan; virtual university; private universities; selectivity process; quality of the university’s teaching staff; ANECA; university reform